Reseña bibliográfica: ¿Qué hacen los mejores profesores de derecho? - Carlin Sanchez, John A. (2018)
The intention of this work is to comment the book titled What the Best Law Teachers Do?, is the result of the collective research work carried out by three American professors over more than four years. The book allows the reader to get into the different law teaching techniques and learning tolls in the United States, starting with different qualifications, attitudes and techniques developed throughout the years by the "best law teachers". The book is composed of ten chapters and four appendixes. In this report I will make a racconto of each of them.